Malawi Economic Monitor, July 2020 : From Crisis Response to a Strong Recovery - World Bank (World Bank, Lilongwe, 2020)
Malawi’s new Government has inherited a difficult situation: the global COVID-19 pandemic has interrupted the country’s trajectory for a third straight year of faster growth, and tackling its impacts will present a considerable challenge. Growth improved to an estimated 4.4 percent in 2019, up from 3.5 percent in 2018, reflecting a rebound in agriculture. Improved agricultural production supported stronger performance in the industrial and service sectors. The uptick in growth also indicated resilience in Malawi’s economy in light of the impact of Cyclone Idai and considerable political uncertainty. The economy was on a trajectory for its third consecutive year of faster growth in 2020 before the onset of the COVID-19 pandemic. The full extent of the epidemic’s negative impact is uncertain as the crisis is still unfolding, but a host of external and internal factors are dampening the Malawi economy. Global factors include both supply and demand channels. Disrupted supply chains have reduced imports of key production inputs, particularly from South Africa and China. However, exports from both countries have partially rebounded after their strict containment measures have been reduced earlier in the pandemic. Preliminary data indicates that imports were 26 percent lower in April and May 2020 compared to the same time last year. Increased trade logistics costs and delays are also affecting the flow of goods through borders. On the demand side, decreased demand from key trade partners is weighing on exports. The tobacco auction season through early July has seen a decrease in sales, with a 11.9 percent reduction in sales values, due to a 14.7 percent reduction in volumes partially offset by a 3.2 percent increase in average price. Tourism has already been severely affected. Remittances (through money transfer) decreased by 57 percent y-o-y in April before rebounding in May, when they were still 15 percent lower than the year prior.